Limited functional effects of subacute syngeneic bone marrow stromal cell transplantation after rat spinal cord contusion injury - Sandner, Beatrice; Ciatipis, Mareva; Motsch, Melanie; Soljanik, Irina; Weidner, Norbert; Blesch, Armin (Cell transplantation, 2016)
Cell transplantation might be one means to improve motor, sensory, or autonomic recovery after traumatic spinal cord injury (SCI). Among the different cell types evaluated to date, bone marrow stromal cells (BMSCs) have received considerable interest due to their potential neuroprotective properties. However, uncertainty exists whether the efficacy of BMSCs after intraspinal transplantation justifies an invasive procedure. In the present study, we analyzed the effect of syngeneic BMSC transplantation following a moderate to severe rat spinal cord injury.
Online prepub date: March 25, 2015
Gesehen am 08.05.2020